Pedo-Transfer Function for Saturated Hydraulic Conductivity of Paddy Soils - Wayayok, Aimrun (2001)
Soil saturated hydraulic conductivity (Ks) is an important soil physical property, especially for determining infiltration rate, irrigation practice, drainage design, run off, deep percolation, groundwater recharge and in simulating leaching and other agricultural and hydrological processes. Several laboratory and field methods can be used to determine Ks. Unfortunately, laboratory and field determinations are usually time consuming, expensive and labour intensive. Deep percolation (DP) is the vertical movement of water beyond the root zone to the water table. It is an important component in the calculation of irrigation requirement and irrigation efficiency. Pedo-transfer functions (PTF) serve to translate the basic information found in the soil survey into a form useful for broader applications through empirical regression-of functional relationships, such as simulation modelling. PTFs have not been applied to paddy soils in the study area. A lot of field measurements will require high labour input hence high cost. This study attempts to simplify the determination of Ks. The main objectives of this study were to seek a simplified method for determining Ks values based on PTF and estimate DP losses in paddy field based on the dominant Ks of the soil profile. Soil samples were collected randomly depending on the soil series within the 2,300 ha Sawah sempadan compartment rice cultivation area. There are five dominant soil series namely, Jawa (Sulfic Tropaquept), Sedu (Typic Suljaquept), Sempadan (Sulfic Tropaquept), Karang (Typic Sulfaquept) and Telok (Typic Suljaquept). Both field work and laboratory work were carried out. The samples were then analysed for the following properties: moisture content in volume basis, bulk density, particle size distribution, organic carbon, pH, electrical conductivity, particle density and moisture content at 33 kPa. The parameters were then used as inputs for developing a Ks model by using SAS (Statistical Analysis System) and SPSS (Statistical Package for Social Science) tools. The Ks values were obtained by using falling head method. Microlysimeter method was adopted to measure the DP loss. The results of the study showed that the high spatial variability of the saturated hydraulic conductivity in the paddy was high. The best regression model for estimating Ks was based on eight soil properties. Five of the eight parameters are the textural attributes, namely clay (C), medium sand (MS), very fine sand (VFS), fine sand (FS) and silt (Si). Others are bulk density (Db), organic carbon (Oe) and moisture content at 33 kPa (8113). The best model fo und from this study was Ks=e(l285-0967 (Dt 8 36x10· 2 (C)+8 55x10 - 2 (OC}-O 134 (MS}-O 943 (Ina 1I3}-O 349 (InVFS)+O 413 (InF5)-2 145 (In51)-0 411 (FS)] (R2 = 0.49). The results of DP study showed that DP loss could be estimated by knowing the average values of Ks of the three layers (topsoil, hardpan and subsoil). DP loss is best related to Ks b y a power function, DP = 3.29 Ks042 (r = 0.60**). These models still need to be further calibrated or validated with other existing data as the input parameters in order to make it more useful.